Road Pricing with Green Vehicle Exemptions: Theory and Evidence - Peter Nilsson; Matthew Tarduno; Sebastian Tebbe (Center for Economic Studies and ifo Institute (CESifo), 2024)
We provide a framework for setting congestion charges that reflect emission and congestion externalities and policy responses, such as vehicle ownership, driving, and residential sorting. Using Swedish administrative microdata, we identify these responses by exploiting a temporary exemption for alternative fuel vehicles and variation in individuals' exposure to congestion charges. We find that commuters respond by adopting exempted alternative fuel vehicles, shifting trips away from fossil fuel toward alternative fuel vehicles, and changing where they live and work. We combine the estimated responses with the framework to recover an optimal congestion charge of exteuro9.46 per crossing in Stockholm.
Keywords: 330